Smart Communities for Future Development: Lessons from Japan - Wongbumru, Tanaphoom; Dewancker, Bart (International Journal of Building, Urban, Interior and Landscape Technology, 2014)
This article aims to review and analyze a content of smart community development that widely used in many cities. The main key is to understand concepts, component, technological approach in various aspects based country’s context. Smart community is able to apply for all development such a physical setting, social dimension, and government perspectives. It does not only focus on technological development approach. From reviewing, it found that smart city has been integrated and modified in terms of spatial planning with smart energy policy and technology application. However, this framework seems difficult to be handled in developing countries due to lacking and limited technology innovation, whereas a stakeholder from policy to practical is still not involved at local and national level.